A REVIEW OF THE EFFECTS OF CONCRETE STRENGTH ON SIZE, SHAPE, AND LOAD - Nitin D. More; Manik. G. Deshmukh; Aaravi.R. Kavade; Abhijeet A. Chavan; Hanumant M.Jadhav; Ajay D.Sawant; KedarR.Jadhav; Janmejay V.Pawar; Harshad D. Paril (International Journal of Innovations in Engineering Research and Technology, 2022)
Concrete characteristics are the most significant and crucial physical material property when reinforced concrete constructions are . Because of the development and in kinds and nature of material utilized to increase the concrete innovation, materialsmix proportions, test measure, mixing strategy, and testing condition have notable affects on highlights of concrete strength, in view of the fact that the control specimen sizes and shapes could be distinct in relation from State to State. Testing of mechanical characteristics (particularly compressive strength and tensile strength) of concrete is one of the most urgent phases of development. To regulate the nature of the concrete, there are several molds used for pouring concrete samples according to various orientations in different nations. Many studies have noticed that the exact shapes and sizes of concrete samples might produce distinct sorts in the repercussions of compressive strength or tensile strength. The relationship between the compressive strength of the concrete cube and the cylinder is complicated. In this paper discuss the Size, Shape and Load Effect on Strength of concrete.